Translation of Stable Compounds and Phraseological Compounds in German Literature - Mamatova Anora Iminovna (International Journal on Integrated Education, 2022)
The main purpose of this article is to show the enrichment of German phraseology and the introduction of phraseological combinations, the process of translation from German to Uzbek. Phraseological combinations are always vividly important phrases. The process of derivation of such compounds is used when words cannot be expressed in the language, thoughts cannot be expressed with other means of speech. Phraseological combinations are used in the press and in the artistic works of writers to express a beautiful idea.